Faktor Lingkungan dan Perilaku yang Berpengaruh Terhadap Kejadian Filariasis Pada Daerah Endemis Filariasis di Kecamatan Maro Sebo Kabupaten Muaro Jambi Propinsi Jambi. - Marzuki, Marzuki; Setiani, Onny; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background : In 2007, Maro Sebo Sub District Muaro Jambi Regency Jambi Province, is one of the endemic filariasis area, with the most dominant filariasis cases in Muaro Jambi Regency. Filariasis is a disease caused by microfilaria and transmitted by mosquitoes as in Indonesia there are three genus of mosquitoes that transmitted the microfilaria : Mansonia Anopheles, Culex and the disease many develope by interaction three factors : vektor host,  agent. As the consequences of the interaction, the microfilaria will infected the limfatic and evoke filaria incidence (filariasis limfatic) in Maro Sebo subdistrict (Untut). Method : The study was an observational study with a case-control approach aimed to find out the relationships between : environmental risk, behaviour, socioeconomic,  knowledge about filariasis and  the incidence of  filariasis. Total samples used for filaria research were 100 respondents, 50 respondents as cases and 50 respondents as control. Result : The result of bivariate analysis revealed that some measured variables were correlated (as risk factor) to the cases of filarias such as : Mansonia genus was the vector filariasis, as knowledge about filariasis (OR = 3,167, CI 95% = 1,349-7,435), used self protection to mosquito bite (OR = 2,495, CI 95% = 1,105–5,629), medical treatmen (OR = 4,041, CI) 95% = 1,215–13,433), use spesification clothes to work (OR = 2,705, CI 95% = 1,197–6,113), work duration (OR = 3,162, CI 95% = 1,032–9,685), and income level (OR = 6,247, CI  95% = 2,257–17,294). The result of multivariat analysis found that the most  potential  variables that influent filariasis are  knowledge about filariasis with a significant value of 0,013 (p<0,05), medical treatment for filariasis with significant value of 0,018 (p<0,05), use of spesific clothes while working with  significant value of 0,003 (p<0,05) and the income level with significant value of 0,008 (p<0,05). Conclusion: Knowledge about filariasis,  traditional traetment, not using spesific clothes while working and respondent minimal income level may increase the prevalence of filariasis. Key word: Enviroment, Behaviour, Filariasis, Muaro Jambi.